ExCo Meeting, Paris (France) 14 November 2022 - (:unkn) unknown (My University, 2022)
This is the material for the Executive Committee Meeting, held in Paris on November 14th, 2022. AGENDA Opening of the meeting Approval of the agenda Approval of the ExCo Meeting Minutes and Resolutions from July 2022 The President’s Report / AESOP Vision Conferences Officer update • AESOP 2023 Head of Schools • AESOP 2023 Congress and PhD Workshop: contract and CMS update • AESOP 2024 Congress and PhD Workshop (Meeting with AESOP 2024 Congress LOC) Secretary General update • Website update: repository • Charter • Upcoming calls - AESOP President (2024 – 2026) - AESOP 2025 Congress and PhD Workshop - AESOP Chair of EEB (2023 – 2026) - AESOP Chair of Best Published Paper Award Committee (2023 – 2028) - AESOP Lecture Series 2023 • Membership update • Core Curriculum update • Transactions update Treasurer Update • Memberships fees overview Young Academics Network Representative’s Report Quality Recognition Report GPEAN Report AOB and Close The item contains the following files (zipped): 02. ExCo Agenda Paris November 2022.docx 03. DRAFT - ExCo Minutes - Tartu - July 2022.docx 03. DRAFT - ExCo Resolutions - Tartu - July 2022.docx 03. Matters arising - ExCo and CoRep July 2022.docx 04 AESOP_President_Report_ExCo_Paris_Nov2022.docx 05_CONFERENCE OFFICER UPDATE_14.11.2022 .pdf 06 2023_ETA prize form.docx 06 AESOP Excellence in Teaching Award_proposed changes.docx 06 AESOP SG Report - ExCo Nov 2022.docx 06. AESOP - InPlanEd mandate - AC signed.pdf 06. Application for AESOP Individual Membership - Huan Tong CV.docx 06. application-form-funding-aesop-tg_TG PSUC.pdf 06. DRAFT - Call for AESOP 2025 Congress and PhD Workshop.docx 06. DRAFT - Call for AESOP Lecture Series 2023.docx 06. DRAFT - Call for AESOP President 2024 - 2026.docx 06. DRAFT - Call for Chair in EEB 2023 - 2026.docx 06. DRAFT - Call for Chair of Best Published Paper Committee 2023 - 2028.docx 06. DRAFT - Call for Chair of Best Published Paper Committee 2023 - 2028 DS.docx 06. InPlanEd original proposal.pdf 06. InPlanEd OTH -Annex1_Gantt.xlsx 06. Ljiljana Radisaljevic six months report 2022-signed.pdf 06. Repository Policy - AESOP Eprints.docx 06. revised Charter 09-11-2022 (input BSP - AC revert).docx 07. TARTU_Treasurer report_sheet_July2022 BUDGET and DETAILS and GRAPHS 10112022.xlsx 08 YA_Report.docx 09 2022 QR Report - ExCo_11_2022_Paris.docx 10 GPEAN REPORT.pdf
Material
Keywords: Agenda; Minutes; Resolution; Matters arising; President report; Conference officer update; ETA prize form; Excellence in Teaching Award proposed changes; SG Report - ExCo; InPlanEd mandate; Application for AESOP Individual Membership - Huan Tong; Application-form-funding-aesop-tg_TG PSUC; Call for AESOP 2025 Congress and PhD Workshop; Call for AESOP Lecture Series 2023; Call for AESOP President 2024 - 2026; Call for Chair in EEB 2023 - 2026; Call for Chair of Best Published Paper Committee 2023 - 2028; Call for Chair of Best Published Paper Committee 2023 - 2028 DS; InPlanEd original proposal; InPlanEd OTH -Annex1_Gantt; Ljiljana Radisaljevic six months report 2022; Repository Policy - AESOP Eprints; revised Charter 09-11-2022 (input BSP - AC revert); TARTU treasurer report 2022 BUDGET and DETAILS and GRAPHS; YA Report; QR Report 2022; GPEAN Report